The modelling of damage due to diffusional creep in high chromium steels - Weyer, Royden (Centre for Materials Engineering, 2017)
Understanding the creep deformation of high chromium steels in use in modern power plants has become important in predicting the behaviour and stability of these materials over their operational lifetime. At the deformation rates and conditions recorded in modern power plants, diffusional creep by vacancy migration is seen to be the dominant creep mechanism. However, the understanding of diffusional creep in particle stabilized materials is heavily incomplete. The aim of this project was to model the damage caused by diffusional creep, while considering the microstructure of high chromium steels and the evolution of this microstructure. This problem is addressed by expanding the existing Nabarro-Herring theory on lattice diffusion into a spatially resolved FEM model using MATLAB. This model focussed on adapting the Nabarro-Herring creep model to handle vacancy concentration changes over time. This allowed the model to produce the primary, secondary and tertiary creep stages present in experimental creep tests. As for microstructure, the focus was on adding precipitates (one of the strongest creep strengthening mechanisms) and voids (the largest cause of material damage). During creep exposure, precipitates were subject to coarsening while voids were subject to growth. The primary creep stage was formed by the initial rapid flux of vacancies into the body of the grain, due to large chemical potential gradients. A dynamic equilibrium of vacancy concentration would form within the grain, leading to the secondary creep stage. The creep rate produced was similar to that of the existing theory and it was found to decrease with the introduction of precipitates. This was evaluated by analysing the stress gradients caused by hard particles in a softer matrix. These stress fields lowered the stress in the grain boundaries and thus resulted in fewer vacancies being generated. Coarsening led to a reduction in the stress field distribution and thus resulted in creep strength loss in the material. The inclusion of voids was shown to decrease the initial creep rate, with void growth lessening this effect and leading to the tertiary creep stage. The initial strengthening was due to the void surface replacing the grain boundary as a source of vacancies. As the void surface is a very inefficient source, fewer vacancies were generated, resulting in lower diffusion rates. A slight steady increase in the creep rate over time was shown with the inclusion of void growth. The increase in vacancy generation was caused by the higher stress fields around voids. Initially the stress increase due to a loss in area was accounted for as a stress concentration around the void. Once this void grew too large in relation to the grain size, the stress concentration no longer accounted for all of the stress increase due to load bearing area loss. This resulted in the damage equation coming into play, causing a rapid increase in the stress throughout the grain and leading to the rapid tertiary creep stage.